Parameters of Quality of Life in Patients with Chronic Obstructive Pulmonary Disease - Салаева М. С.; Худайберганова Н. Х.; Ходжиматова И. Х. (Scholars Digest Publishing, 2023)
The aim of our work was to assess the impact of individual and group training on the autonomic nervous system and quality of life in patients with chronic obstructive pulmonary disease (COPD).
Keywords: quality of life parameters, patients with COPD.